Rotational symmetry in ribonucleotide strand requirements for binding of HIV-1 Tat protein to TAR RNA. - Barnett, R W (1993)
Transactivation of human immunodeficiency virus (HIV) gene expression requires binding of the viral Tat protein to a RNA hairpin-loop structure (TAR) which contains a two or three-nucleotide bulge. Tat binds in the vicinity of the bulge and the two adjacent duplex stems, recognising both specific sequence and structural features of TAR. Binding is mediated by an arginine-rich domain, placing Tat in the family of arginine-rich RNA binding proteins that includes other transactivators, virus capsid proteins and ribosome binding proteins. In order to determine what features of TAR allow Tat to bind efficiently to RNA but not DNA forms, we examined Tat binding to a series of RNA-DNA hybrids. We found that only one specific strand in each duplex stem region needs to be RNA, implying that interaction between Tat and a given stem may be solely or predominantly with one of the two strands. However, the essential strand is not the same one for each stem, suggesting a switch in the bound strand on opposing sides of the bulge.